2013
DOI: 10.1161/circresaha.112.300626
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cholesterol Metabolism and Plasma High-Density Lipoprotein Levels by microRNA-144

Abstract: Rationale Foam cell formation due to excessive accumulation of cholesterol by macrophages is a pathological hallmark of atherosclerosis, the major cause of morbidity and mortality in Western societies. Liver X nuclear receptors (LXRs) regulate the expression of the adenosine triphosphate-binding cassette (ABC) transporters, including ABCA1 and ABCG1. ABCA1 and ABCG1 facilitate the efflux of cholesterol from macrophages and regulate high-density lipoprotein (HDL) biogenesis. Increasing evidence supports the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(168 citation statements)
references
References 36 publications
3
159
0
6
Order By: Relevance
“…The depressed expression of miR-122 effectively reduces the cholesterol content in the serum [44]. Furthermore, the targeted control of ssc-miR-144 and ssc-miR-758 to the ATP-binding cassette sub-family A member 1 (ABCA1) gene results in an indirect regulation of the metabolism of cholesterol [45,46]. ssc-miR-204 inhibits the Runx2 gene, thus, accelerating the adipogenic differentiation of MPCs and BMSCs [47], and the upregulation of ssc-miR-204, in this study, indicates that it may activate adipocyte differentiation in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The depressed expression of miR-122 effectively reduces the cholesterol content in the serum [44]. Furthermore, the targeted control of ssc-miR-144 and ssc-miR-758 to the ATP-binding cassette sub-family A member 1 (ABCA1) gene results in an indirect regulation of the metabolism of cholesterol [45,46]. ssc-miR-204 inhibits the Runx2 gene, thus, accelerating the adipogenic differentiation of MPCs and BMSCs [47], and the upregulation of ssc-miR-204, in this study, indicates that it may activate adipocyte differentiation in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The present result of a greater than fourfold increase in bta-miR-202 levels between 9-11 and 15-17 mm healthy follicles builds on those earlier findings by indicating a role for this miRNA during folliculogenesis in the adult bovine ovary. In addition to mir-202, biological roles for the clustered mir-144 and mir-451 have also been proposed, but only in relation to non-ovarian cells; those include regulatory roles in erythropoiesis (Pase et al 2009), differentiation of vascular smooth muscle cells (Turczyń ska et al 2013) and, potentially relevant during follicular differentiation, cholesterol trafficking in macrophages (Ramirez et al 2013). Interestingly, both miR-144 and miR-451, as well as miR-652, were upregulated in rat ovaries following an ovulatory hCG bolus, although no attempt was made to identify the specific cell type(s) involved (Kitahara et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ramírez and colleagues demonstrated that T0901317 increases miR-144 expression in macrophages and mouse livers. The overexpression of miR-144 reduces ABCA1 expression, while the silencing of miR-144 in mice increases the expression of ABCA1 and plasma HDL levels (Ramirez et al, 2013). Thus,…”
Section: Future Perspectives and Conclusionmentioning
confidence: 97%